ANALYSIS OF GOOD AND CORRECT LANGUAGE SKILLS AMONG REGIONAL STUDENTS - Amorita, Nessie Illona (Politeknik Negeri Bengkalis, 2024)
In the current era of development, mastery of language skills has become increasingly crucial considering that communication has become a very important aspect in modern life. This research aims to analyze good and correct language skills among regional students using a qualitative descriptive method approach. The research subjects were students from various ethnic groups in Indonesia who studied at the Indragiri Hulu Institute of Technology and Business, selected using a purposive sampling technique. Data collection was carried out through observation, interviews and documentation studies. Qualitative data analysis includes data condensation, data presentation, and drawing conclusions/verification. The research results show that there are still many regional students who do not have good and correct language skills. This research also examines the importance of Indonesian as a unifier of the nation, views on the essence of good and correct use of Indonesian in the campus environment, its influence and benefits for students from various ethnic backgrounds, responses to the use of regional languages on campus, factors causing pronunciation difficulties good and correct Indonesian, as well as efforts to increase the use of Indonesian in the campus environment. Keywords: Language Skills, Indonesian, Regional Students.